2016
DOI: 10.1002/vms3.30
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of rabies and response to dog bites in a Bangladesh community

Abstract: Community awareness regarding rabies and treatment seeking behaviours are critical both for the prevention and control of the disease in human and animals. We conducted a study to explore people's awareness about rabies, their attitudes towards dogs and practices associated with treating dog bites in Satkhira Sadar, a south‐western sub‐district of Bangladesh. Of the total 3200 households (HHs) surveyed, the majority of the respondents have heard about rabies (73%) and there was a high level of awareness that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
55
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 15 publications
12
55
8
Order By: Relevance
“…The epidemiological characteristics of human rabies cases found in this study were similar to those reported elsewhere in Bangladesh and neighbouring countries. Our study revealed that rabies victims were mostly males of www.nature.com/scientificreports www.nature.com/scientificreports/ less than 15 years of age, which is similar to some other studies in Bangladesh and neighbouring countries 14,16,31 . The bite locations were mostly on the patients' lower limbs, with the majority of the bites being category III 4 .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The epidemiological characteristics of human rabies cases found in this study were similar to those reported elsewhere in Bangladesh and neighbouring countries. Our study revealed that rabies victims were mostly males of www.nature.com/scientificreports www.nature.com/scientificreports/ less than 15 years of age, which is similar to some other studies in Bangladesh and neighbouring countries 14,16,31 . The bite locations were mostly on the patients' lower limbs, with the majority of the bites being category III 4 .…”
Section: Discussionsupporting
confidence: 90%
“…Our analysis showed that the majority of the rabies victims primarily sought treatment from traditional healers following animal exposure, with no history of taking any PEP. Previous studies in Bangladesh revealed that a good number of animal bite victims first sought treatment from traditional healers instead of taking any modern PEP 16 . These sorts of health-seeking behaviour might be attributed to persevering myths and dogmas among the people of the community, poor socio-economic status, lack of proper education, lack of accessibility and affordability of PEP treatment in local government hospitals, distance to government hospitals from the victims' residence, etc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations